2013
DOI: 10.1093/abbs/gmt082
|View full text |Cite
|
Sign up to set email alerts
|

α-Linolenic acid attenuates doxorubicin-induced cardiotoxicity in rats through suppression of oxidative stress and apoptosis

Abstract: Doxorubicin (DOX), a widely used anti-tumor drug, can give rise to severe cardiotoxicity by oxidative stress and cell apoptosis, which restricts its clinical application. α-Linolenic acid (ALA) has been shown to serve as a potent cardioprotective agent. The aim of this study was to explore the protective effects of ALA on DOX-induced cardiotoxicity and the underlying molecular mechanisms for this cardioprotection in rats. Rats were randomly divided into four groups and administrated with normal saline, ALA (50… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

11
53
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(64 citation statements)
references
References 39 publications
11
53
0
Order By: Relevance
“…The results of the present study showed a significant increase of cardiac TBARS content with decrease of anti-oxidants in DOX-treated rats (Figures 1 and 2), suggesting the primary role of oxidative stress in DOX cardiotoxicity. These data are in agreement with earlier studies (Yu et al 2013). Moreover, the reactive oxygen species (ROS) leads to depletion of the endogenous antioxidant system and oxidative injury.…”
supporting
confidence: 94%
See 3 more Smart Citations
“…The results of the present study showed a significant increase of cardiac TBARS content with decrease of anti-oxidants in DOX-treated rats (Figures 1 and 2), suggesting the primary role of oxidative stress in DOX cardiotoxicity. These data are in agreement with earlier studies (Yu et al 2013). Moreover, the reactive oxygen species (ROS) leads to depletion of the endogenous antioxidant system and oxidative injury.…”
supporting
confidence: 94%
“…In the current work, our results revealed that DOX could induce cardiomyocyte apoptosis, as evaluated by decreased Bcl-2 and increased Bax gene expression (Figures 4 and 5), suggesting that apoptosis is one of the major contributors of DOX-imposed cardiac toxicity. These results were in agreement with previous studies (Yu et al 2013). Accumulated data suggest that cardiomyocyte apoptosis and death in response to DOX are mainly mediated by increased oxidative stress (Smith et al 2010).…”
supporting
confidence: 93%
See 2 more Smart Citations
“…Moderation of inflammatory factors helps Rg3 to antagonize ADM-Induced cardiotoxicity from oxidative stress. previous reports revealed that ADM-induced cardiotoxicity is associated with multiple signaling pathways (Kotamraju et al 2000;Negoro et al 2001;Yu et al 2013). The transcription factor Nrf2 plays a central role in the inducible expression of many cytoprotective genes in response to oxidative stresses (Taguchi et al 2011).…”
Section: Discussionmentioning
confidence: 99%